Cognitive behavioral intervention for trauma in adolescent girls in child welfare: A randomized controlled trial. (December 2020) - Auslander, Wendy; Edmond, Tonya; Foster, April; Smith, Penny; McGinnis, Hollee; Gerke, Donald; Tlapek, Sarah; Threlfall, Jennifer; Voth Schrag, Rachel; Dunn, Jerry; Jonson-Reid, Melissa
Highlights: CBITS is effective for reducing PTSD and depression for girls in child welfare. CBITS is more effective than usual care for increasing problem-solving skills. Program satisfaction and attendance of participants were high. Abstract: Objective: This study tested the effectiveness of Cognitive Behavioral Intervention for Trauma in Schools (CBITS) in adolescent girls involved in the child welfare system. Three outcomes were evaluated: symptoms of posttraumatic stress disorder (PTSD), depression, and social problem-solving skills. Method: A randomized controlled trial was utilized to compare the effects of an adapted version of CBITS with usual care (UC) services. Participants were ages 12 to 19 ( N = 249), the majority of whom (69.5%) were African American. Participants' symptoms of PTSD, depression, and social problem-solving skills were evaluated at pre, post (3 months), and follow-up (6 months) assessments. Linear mixed models were used to compare condition by time interactions using all available data. Control variables were demographics, service use, and number of types of traumas. Treatment fidelity, participant acceptability, and satisfaction with the intervention were also examined. Results: Analyses indicated that participants in the CBITS condition showed significantly greater increases in social problem-solving than the UC condition. For both PTSD and depression symptoms, there were no significant differences between the two conditions. Both the CBITS and UC participants showed significant reductions in symptoms. Results also indicated that this intervention is an acceptable model for this population. Conclusions: Despite the growth of trauma-focused, evidence-supported interventions for reducing PTSD and depression, knowledge of effective interventions in child welfare youth lags behind. Because CBITS is more effective than UC in increasing social problem-solving skills, this intervention may be an important treatment option for this population.